2023
DOI: 10.3390/app13137503
|View full text |Cite
|
Sign up to set email alerts
|

Digital Twin to Control and Monitor an Industrial Cyber-Physical Environment Supported by Augmented Reality

Abstract: Increasing industrial development and digital transformations have given rise to a technology called Digital Twin (DT) that has the potential to break the barrier between physical and cyberspace. DT is a virtual and dynamic model enabled through a bidirectional data flow that creates high-reliability models with interconnection and fusion between the physical and digital systems for full integration. In smart manufacturing, this technology is increasingly used in research and industry. However, the studies con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
2
7
0
Order By: Relevance
“…The results showed that the proposed DT provides a more complete understanding of the modeled process, with real-time interaction and dynamic visualization allowing for improved decision-making. In [28], they implemented a DT for the control and monitoring of a process with AR; the system was implemented in a modular production station MPS 500. The architecture consists of a PLC and a Raspberry Pi for sending process data to the cloud using Modbus TCP/IP and the M2M protocol; subsequently, the data are sent from the RPI to Unity for the development of the DT application for visualization and control via AR.…”
Section: Related Workmentioning
confidence: 99%
“…The results showed that the proposed DT provides a more complete understanding of the modeled process, with real-time interaction and dynamic visualization allowing for improved decision-making. In [28], they implemented a DT for the control and monitoring of a process with AR; the system was implemented in a modular production station MPS 500. The architecture consists of a PLC and a Raspberry Pi for sending process data to the cloud using Modbus TCP/IP and the M2M protocol; subsequently, the data are sent from the RPI to Unity for the development of the DT application for visualization and control via AR.…”
Section: Related Workmentioning
confidence: 99%
“…In case of potential security risks, they rapidly issue alerts, enabling immediate countermeasures to be taken. This sensor network not only monitors equipment operation and identifies normal functioning but also provides historical data records [10], facilitating post-event analysis and tracing, and effectively preventing potential faults and accidents. The wireless sensor network is composed of a 5G Radcap network, Zigbee network, Bluetooth network, and Wifi network.…”
Section: Ironmaking Plant Dynamic Security Assessment System Design T...mentioning
confidence: 99%
“…where: 'G' is a constant (10), and 'P' is the rate of injuries per thousand employees. Assuming the ironmaking plant's injury rate is 3/1000, the initial security risk level of the ironmaking plant is 58.09.…”
Section: Hidden Layermentioning
confidence: 99%
“…With regard to the integration of DT into CPS a multitude of studies have been advanced. In particular, the research conducted by study [22] employed a rigorous methodology to acquire pertinent data on the physical processes, establish a digital representation of the environment, facilitate seamless communication between the physical and virtual realms, employ simulation models within the digital framework, and dynamically parameterize the simulation environment in real-time based on the ongoing physical processes. The utilization of an AR application was employed for the purpose of variable control, establishing an intuitive operational environment for process management.…”
Section: Related Workmentioning
confidence: 99%
“…The seamless synchronization between the virtual reality representation and the actual physical environment is achieved through the utilization of the OPC program known as KEPServerEX, coupled with the transformation of twin data into the JSON format. It is noteworthy that an increasing number of studies have adopted the OPC-UA protocol [22,29,30] as a means of harmonizing the real and physical realms, with the overarching objective of diminishing latency times.…”
Section: Related Workmentioning
confidence: 99%